Do Life-Cycles Affect Financial Reporting Quality? Evidence from Emerging Market - Gökberk Can (Cogent Business & Management, 2020)
This paper aims to present the effect of life cycle on financial reporting quality (FRQ). Discretionary accruals, small profit, and audit aggressiveness were used to test the FRQ from different approaches for Borsa Istanbul-listed companies between 2008 and 2017. The sample comprises 1,645 observations of 217 companies over a 9 year period. The life stages were estimated with Dickinson's cash-flow patterns. Following Hansen, Hong and Park⁠, introduction, growth, mature, shake-out, and decline parameters were assigned values of 0, 0.25, 0.5, 0.75, and 1, respectively. The findings for small profit and discretionary accruals are consistent with those of previous literature. Results show that both discretionary accruals and small profit decrease as the companies move forward in their life cycles, while, on the other hand, audit aggressiveness increases. A negative coefficient was observed, but it was insignificant for the other dependent variables. The findings provide insight into the effect of life-cycle stages on FRQ. Results show that the introduction and decline stages negatively affect FRQ, and in addition showed that the audit aggressiveness of Turkish companies decreases with increased listing duration.
Keywords: 650; life-cycle stages; financial reporting quality; discretionary accruals